The Role and Benefits of Seamless Learning in Improving Primary School Children’s Learning Achievement - Wa Ode Riniati (Yayasan Adra Karima Hubbi, 2024)
Background. Technological advancements have revolutionized education, particularly in elementary schools, offering novel avenues for learning. Seamless Learning, by seamlessly blending classroom and digital learning experiences, emerges as a promising avenue to enhance elementary students’ academic success. Purpose. This research aims to identify effective learning strategies and models using the Seamless Learning approach. Through a deeper understanding of how technology and an integrated learning environment can influence learning outcomes, it is hoped that concrete recommendations will emerge to improve learning practices in elementary schools. Method. This study uses quantitative surveys to assess Seamless Learning’s effect on elementary students’ academic success. It involves 30 PGSD and PGMI students who completed the PPL, alongside experienced SD teachers. Data collection occurs through WhatsApp questionnaires, with analysis conducted using the Miles Huberman model. Results. The results of the questionnaire analysis showed that the majority of respondents expressed positive perceptions of the use of Seamless Learning in school children’s learning base. The majority of respondents use technology regularly, feel enthusiastic, and feel improvements in understanding, applying, and improving their learning achievement through this approach. Conclusion. Overall, this research confirms the great potential of using Seamless Learning in increasing student engagement and learning achievement in school base. However, continuous efforts are needed to optimize the use of Seamless Learning so that it can provide maximum benefits for learning in elementary schools, as well as prepare students to better face the demands of the modern world.